Network-Specific Corticothalamic Dysconnection in Attention-Deficit Hyperactivity Disorder. Issue 2 (February 2021) - Hua, Mao-Hsiu; Chen, Yen-Ling; Chen, Mu-Hong; Huang, Kai-Lin; Hsu, Ju-Wei; Bai, Ya-Mei; Tsai, Shih-Jen; Wu, Yu-Te
ABSTRACT: Background: Functional connectivity (FC) is believed to be abnormal in attention-deficit hyperactivity disorder (ADHD). Most studies have focused on frontostriatal systems, and the role of the thalamic network in ADHD remains unclear. The current study used FC magnetic resonance imaging (fcMRI) to explore corticothalamic network properties and correlated network dysconnection with ADHD symptom severity. Methods: Eighteen adolescents with ADHD and 16 healthy controls aged 12 to 17 years underwent resting functional MRI scans, clinical evaluations, and 2 parent rating scales, namely the Swanson, Nolan, and Pelham IV scale and the Child Behavior Checklist. Six a priori cortical regions of interest were used to derive 6 networks: the dorsal default mode network, frontoparietal network, cingulo-opercular network (CON), primary sensorimotor network (SM1), primary auditory network, and primary visual network (V1). The corticothalamic connectivity for each network was calculated for each participant and then compared between the groups. We also compared the 2 scales with the network connectivity. Results: The corticothalamic connectivity within the CON was significantly reduced ( p < 0.05) among adolescents with ADHD compared with the controls. The corticothalamic dysconnection within the CON, SM1, and V1 networks negatively correlated with ADHD symptom severity. Conclusion: This network analysis indicates that corticothalamic dysconnection in ADHD involves the CON, SM1, and V1 networks and relates to symptom severity. The findings provide evidence of dysfunctional thalamus-related networks in ADHD. Abstract : This article has supplementary material on the web site: www.jdbp.org.